2001
DOI: 10.1159/000049962
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Therapy for the Subfertility of Cryptorchidism

Abstract: Background: The subfertility of cryptorchidism correlates with severely reduced total germ cell counts in prepubertal testicular biopsies of undescended testes. Reduced total germ cell counts are associated with defects in the two prepubertal steps in maturation and proliferation in germ cells: first, the transformation of the fetal stem cell pool (gonocytes) into the adult stem cell pool (adult dark spermatogonia) at two to three months of age and, second, the transformation of adult dark spermatogonia into p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 17 publications
(7 reference statements)
0
30
0
Order By: Relevance
“…Analyzed in full, at least half of the cryptorchid population is depleted of Ad spermatogonia. The preliminary results of treating cryptorchid boys with low total germ cell count, and lacking Ad spermatogonia, with LH-RH analog are encouraging [16,17,18,19]. Particularly, for boys younger than age seven, having no Ad spermatogonia, as assessed by biopsies performed during orchidopexy, and for whom the total number of germ cells is <0.2 per tubular cross-section, will profit from LH-RHa treatment which will increase the number of germ cells significantly [18].…”
Section: Discussionmentioning
confidence: 99%
“…Analyzed in full, at least half of the cryptorchid population is depleted of Ad spermatogonia. The preliminary results of treating cryptorchid boys with low total germ cell count, and lacking Ad spermatogonia, with LH-RH analog are encouraging [16,17,18,19]. Particularly, for boys younger than age seven, having no Ad spermatogonia, as assessed by biopsies performed during orchidopexy, and for whom the total number of germ cells is <0.2 per tubular cross-section, will profit from LH-RHa treatment which will increase the number of germ cells significantly [18].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Huff et al [ 38 ] reported that GnRH treatment after orchidopexy improved total germ cell counts in 75 % of the patients. These results have partly been confi rmed by other groups.…”
Section: Adjunctive Therapymentioning
confidence: 96%
“…Alternative medicines in plants, fungi, and insects have been studied to enhance sexuality (Crimmelet al, 2001). In fact, the injection of testosterone to restore the reproductive function has been applied to treat men with insufficient testosterone secretion for decades (Huff et al, 2001). The scientific evidence related to the mechanisms or efficacy of these alternatives is scarce or often unconvincing.…”
Section: Introductionmentioning
confidence: 99%